Improving A/B Testing on the Basis of Possibilistic Reward Methods: A Numerical Analysis - Miguel Martín (MDPI AG, 2021)
A/B testing is used in digital contexts both to offer a more personalized service and to optimize the e-commerce purchasing process. A personalized service provides customers with the fastest possible access to the contents that they are most likely to use. An optimized e-commerce purchasing process reduces customer effort during online purchasing and assures that the largest possible number of customers place their order. The most widespread A/B testing method is to implement the equivalent of RCT (randomized controlled trials). Recently, however, some companies and solutions have addressed this experimentation process as a multi-armed bandit (MAB). This is known in the A/B testing market as dynamic traffic distribution. A complementary technique used to optimize the performance of A/B testing is to improve the experiment stopping criterion. In this paper, we propose an adaptation of A/B testing to account for possibilistic reward (PR) methods, together with the definition of a new stopping criterion also based on PR methods to be used for both classical A/B testing and A/B testing based on MAB algorithms. A comparative numerical analysis based on the simulation of real scenarios is used to analyze the performance of the proposed adaptations in both Bernoulli and non-Bernoulli environments. In this analysis, we show that the possibilistic reward method PR3 produced the lowest mean cumulative regret in non-Bernoulli environments, which proved to have a high confidence level and be highly stable as demonstrated by low standard deviation measures. PR3 behaves exactly the same as Thompson sampling in Bernoulli environments. The conclusion is that PR3 can be used efficiently in both environments in combination with the value remaining stopping criterion in Bernoulli environments and the PR3 bounds stopping criterion for non-Bernoulli environments.